Trends and drivers of blindness and vision loss burden attributable to age-related macular degeneration from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Ran Zhang; Xiaojing Zhang; Yun Gao; Zhongming Zhang (BMJ Open, 2025)
Objectives To investigate the trends and drivers of the burden of blindness and vision loss (BVL) attributable to age-related macular degeneration (AMD) from 1990 to 2021.Design Cross-sectional study.Setting Studies from the Global Burden of Disease (GBD) Study 2021 database, generated from population-representative data sources identified through a literature review and research collaborations, were included.ParticipantsBVL attributable to AMD participants.Outcomes Total numbers and age-standardised rates of prevalence and disability-adjusted life years (DALYs) were the main outcomes. Secondary outcomes consisted of the temporal trends in the BVL burden attributable to AMD at global, regional and national levels, using an age-period-cohort model, and factors influencing changes in BVL burden attributable to AMD, using decomposition analysis.Results Age-standardised prevalence and DALY rates of BVL attributable to AMD showed a decreasing trend, with a global net drift in prevalence of −0.35% (95% CI: −0.38 to −0.32) per year. Globally, we observed unfavourable age effects, subtle period effects and positive cohort effects on prevalence. Over the past three decades, the global increase in prevalence and DALYs of BVL attributable to AMD was primarily due to population growth and ageing.Conclusions Our research indicates that the population growth and ageing have exacerbated the burden of BVL attributable to AMD over the past 30 years. We identified countries with substantial room for improvement and those with exemplary performance to inspire potential ideas for better managing BVL attributable to AMD.